Study protocol for a pilot randomised controlled trial of a virtually delivered behavioural intervention (ACTION) for adults with cancer at risk for opioid use disorder - James A Tulsky; Joseph A Greer; Emanuele Mazzola; Miryam Yusufov; William F Pirl; Kristy L. Dalrymple; Ilana M Braun; R. Kathryn McHugh (BMJ Open)
Introduction Opioid therapy is often central to pain management during cancer care. However, opioid exposure and unaddressed psychological suffering jointly amplify opioid use disorder risk. Therefore, we iteratively developed a behavioural, individually delivered intervention to mitigate the risk of opioid use disorder during cancer care (Acceptance and Commitment Therapy Intervention when Opioids are Necessary (ACTION)).Methods and analysis This is a single-site, non-blinded, randomised, controlled pilot trial of ACTION compared with a waitlist control group. The aims of this study are to examine the feasibility (defined as an overall enrolment rate of ≥60% and a retention rate of >75%) and acceptability (assessed via patient-reported feedback in exit interviews and Client Satisfaction Questionnaire-8 ratings) of ACTION (primary outcomes) and to assess changes in participant-reported depression, anxiety and opioid misuse (secondary outcomes). Patients will be recruited from Dana-Farber Cancer Institute (Boston, Massachusetts, USA). The total number of patients completing the study will be 40. All patients will complete baseline and follow-up measures after 6 weeks. Patients randomly assigned to ACTION (n=20) will receive six weekly 30-min sessions delivered by a mental health provider either via telehealth or in-person. Patients assigned to the waitlist control group (n=20) will be offered the intervention on completion of their follow-up assessments, approximately 6 weeks (±2 weeks), following baseline.Ethics and dissemination This study is approved by the Dana-Farber/Harvard Cancer Center Institutional Review Board (Protocol #21-587). Participants provide either written or electronic informed consent on study approach and once enrolled, they can withdraw from the study at any time. Results will be published in peer-reviewed journals and presented at scientific meetings.Trial registration number NCT05643027.